EMPOWERING COMMUNITIES FOR CLIMATE CHANGE ADAPTATION: INSIGHTS FROM PEKANBARU'S CLIMATE VILLAGE PROGRAM - Latip, Latip; Saputra, Trio (Universitas Padjadjaran, 2025)
This study presents a qualitative analysis that highlights a significant lack of knowledge regarding the lasting impact of community-led climate adaptation initiatives. It specifically examines the success of the Climate Village Program (ProKlim) in Tobek godang Village, Pekanbaru City, Indonesia. Although the program has been adopted across the entire country, there has been a lack of extensive research on its potential to be maintained over time and its effects on a local scale. This study provides a comprehensive evaluation of the selected village in Pekanbaru that has been awarded five ProKlim certificates, comprising of three main and two middle certificates of recognition. Data were gathered by systematic observations and comprehensive interviews with influential individuals involved in the matter. The findings suggest that Tobek godang Village has successfully implemented measures to adapt to and mitigate the impacts of climate change, including flood control, waste management, and urban greening. However, there are still some ongoing difficulties that need to be addressed. The program's ideal performance is hindered by inadequate finance, insufficient expert support, and a lack of socialization. Notwithstanding these obstacles, the village's accomplishments in community mobilization and environmental awareness are praiseworthy. The analysis recommends that the government and other stakeholders should increase their efforts to allocate funding and give expertise in order to improve program outcomes. This study provides insights into how grassroots climate programs might be scaled up in other vulnerable places. This contributes to the broader discussion on building resilience to climate change and promoting community-based environmental act.